The role of 0-10 m sprint ability as a predictor for holistic talent development in an english football academy - Kelly, A. L.; Williams, C. A.; Wilson, M. R. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Physical performance characteristics, such as sprinting, jumping, and agility, have been found to influence elite youth football development towards professional status in European countries such as Austria (Gonaus & Muller. 2012), Belgium (Deprez ef al. (2015). Finland (Forsman ef al.. 2016), Germany (Honer <§ Votteler, 2016), Holland (Huijgen ef al., 2014). Portugal (Coelho-e-Silva ef al., 2010). Serbia (Mirkov et al.. 2010), Spain (Gil et al.. 2007), and Switzerland (Zuber ef al.. 2016). However, little is known what physical performance factors influence talent development within an English context. Subsequently, the aim of this study was to determine, over two consecutive football seasons, what fitness testing outcomes were associated with greater holistic development within the Youth Development Phase (YDP; under-12 to 16s) in an English football academy. Methods: A total of 51 players (aged 11 to 17 years) completed a collection of f ive football-specific fitness tests twice across two seasons to observe physical performance; 0-10 m sprint. 0-30 m sprint. 10-30 m sprint, countermovement jump (CMJ), and L-agility. Holistic development was measured by comparing the delta change between overall player profile scores from two seasonal player reports, including psychological, physiological, technical, and tactical attributes. Stepwise regression analyses were conducted to assess the predictive capability of these variables on overall development, with statistical significance set atp=0.05. Results: Only 0-10 m sprint ability was negatively associated with holistic development (r^O.092, p=0.031). explaining 9.2% of the variance. Thus. 0-30 m sprint. 10-30 m sprint. CMJ. and L-agility results had no association with holistic development. Conclusion: Whilst these findings were dissimilar from previous studies (Forsman et al., 2016: Zuber et al., 2016; Gonaus & Muller. 2012; Mirkov et al.. 2010), they coincide with others who also found shorter sprint ability as a significant feature within the talent development process in elite youth football (Honer & Votteler. 2016; Deprez ef al.. 2015; Huijgen ef al.. 2014; Coelho-e-Silva ef al.. 2010; Gil et al.. 2007). The importance of 0-10 m sprint ability in the modern game is illustrated by Barnes ef al. (2014). who reveal the number of sprints has increased by 35% in the English Premier League, whilst the proportion of explosive sprints has also improved, alongside sprint distance becoming shorter, over a seven season period between 2006/07 and 2012/13. Additionally. Faude ef al. (2012) highlight the importance of straight line sprinting at senior professional level, as it`s the most frequent physical action used in goal situations in professional football. Therefore, it is proposed the measurement of 0-10 m sprint ability is included in a batch of testing procedures to identify, and subsequently monitor, athlete development within an English football academy setting. In addition. 0-10 m sprints should be incorporated into football-specific training strategies within the YDP to facilitate holistic development.